2021
DOI: 10.3390/ijms22094878
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes Modify Leaf Micromorphology, Chloroplast Ultrastructure and Photosynthetic Activity of Pea Plants

Abstract: Single-walled carbon nanotubes (SWCNTs) emerge as promising novel carbon-based nanoparticles for use in biomedicine, pharmacology and precision agriculture. They were shown to penetrate cell walls and membranes and to physically interact and exchange electrons with photosynthetic complexes in vitro. Here, for the first time, we studied the concentration-dependent effect of foliar application of copolymer-grafted SWCNTs on the structural and functional characteristics of intact pea plants. The lowest used conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…It should be noted that in these experiments SWCNT were either applied on a leaf surface with compromised epidermis or infiltrated into the leaves, thus omitting the barrier properties of cuticular waxes. The results of our recent work, however, suggest penetration of SWCNT into chloroplasts upon non-invasive foliar application of polymer-grafted SWCNT [ 12 ] which was also applied in this work.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It should be noted that in these experiments SWCNT were either applied on a leaf surface with compromised epidermis or infiltrated into the leaves, thus omitting the barrier properties of cuticular waxes. The results of our recent work, however, suggest penetration of SWCNT into chloroplasts upon non-invasive foliar application of polymer-grafted SWCNT [ 12 ] which was also applied in this work.…”
Section: Discussionmentioning
confidence: 97%
“…The retarded fluorescence rise in the J-I and I-P phases might be due to downregulation of electron transport through Cyt b 6 f known to be a subject of ‘photosynthetic control’ by thylakoid lumen acidity [ 28 ]. Our recent study demonstrates that the proton motive force in SWCNT 300 treated plants was slightly lower than in control plants [ 12 ] indicating that the slower increase of Chl fluorescence in the J-P phase is not due to Cyt b 6 f control. It is still to be cleared out if SWCNT are capable of pulling electrons at the PSI or Cyt b 6 f level or the observed phenomenon represents indirect effect of the SWCNT treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the increase in total chlorophyll content observed at low doses of MWCNTs/PVP (Table 4 ) may result from the increased photosynthetic activity 57 , 58 . Velikova et al 59 observed that SWCNTs could alter pea plants' leaf micromorphology and chloroplast ultrastructure, thereby affecting their photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%